Gingival tissue proliferation into the tooth following iatrogenic miniscrew insertion: A newer underreported complication - Thavarajah Rooban; Nathamuni Rengarajan Krishnaswamy; Valai Kasim Shakeel Ahmed (Wolters Kluwer Medknow Publications, 2017)
Miniscrew implant (MSI) has been reported to be an excellent, supportive orthodontic anchorage tool. The placement of MSI is not free from complication and foremost of which is penetration of MSI into the vital tooth structures. This case report is probably the first to report a newer underreported complication. Interestingly, a small bit of gingival tissue was found deep inside the dentin of the tooth, surviving and proliferating in the MSI-damaged zone. This case report is probably the first to give direct histological evidence in humans that a MSI can cause implantation phenomenon which has the potential to give rise to numerous pathologies including pulpal, periodontal, and cystic transformation. Through this report, it is emphasized that clinicians should have a structured, formal MSI placement training to avoid such instances and also underlines the need to develop protocols to be followed in the instance of an inadvertent MSI penetration.